2010
DOI: 10.1002/cncr.25314
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes in patients with intermediate‐sized hepatocellular carcinoma

Abstract: BACKGROUND:To improve the efficacy of radiofrequency ablation (RFA) for the treatment of intermediate-sized hepatocellular carcinomas (HCCs), the authors compared RFA combined with transcatheter arterial chemoembolization (TACE) to RFA alone. METHODS: The authors randomly assigned 37 patients with solitary HCCs (diameter, 3.1-5.0 cm in the greatest dimension) to 2 groups: the TACE-RFA group, in which the patients received TACE followed by RFA on the same day, and the RFA group, in which the patients received o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(104 citation statements)
references
References 46 publications
4
93
1
Order By: Relevance
“…In the aspect of RFA techniques, overlapping technique and combined treatment with transcatheter arterial chemoembolization can be used. [7][8][9] Another strategy is to use switching monopolar, bipolar or multipolar modes to deliver radiofrequency (RF) energy more efficiently. 10,11 Sufficient ablation margin can also be achieved by more efficient electrodes: internally cooled electrode increases the size of ablation zone by preventing charring around the electrode tip.…”
Section: Discussionmentioning
confidence: 99%
“…In the aspect of RFA techniques, overlapping technique and combined treatment with transcatheter arterial chemoembolization can be used. [7][8][9] Another strategy is to use switching monopolar, bipolar or multipolar modes to deliver radiofrequency (RF) energy more efficiently. 10,11 Sufficient ablation margin can also be achieved by more efficient electrodes: internally cooled electrode increases the size of ablation zone by preventing charring around the electrode tip.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted in Korea evaluated the therapeutic efficacy of RFA plus TACE in patients with medium-sized (3.1-5.0 cm) HCCs and found that it significantly lowered the local tumor progression rate compared with RFA alone (55% and 86% at 5 years, respectively; P < 0.001) [135] . Subsequently, several randomized controlled trials compared RFA and RFA plus TACE in Japan and China [136,137] , and a meta-analysis of these studies showed that the combined treatment was significantly associated with higher overall survival (OR = 1.85, 95%CI: 1.26-2.71) and recurrence-free survival (OR = 2.13, 95%CI: 1.41-3.20) rates [138] . The benefits of the combination therapy could be attributed to the avoidance of the heat sink effect and the subsequent increase in the size of the thermal coagulation zone.…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
“…The rationale behind lipiodol TACE-preceded RFA is as follows: a state of transient liver infarction is induced by the lipiodol, which regurgitates into the portal branches via the peribiliary venous plexus, thereby decreasing the heat sink effect, expanding the ablative area, and promoting the ablation of satellite lesions [46] . Several studies have reported significantly better survival rates with TACE-preceded RFA compared to RFA alone for intermediate-sized lesions [45,[47][48] . In another administration method, TACE may follow RFA, with TACE expected to handle the peripheral part of a tumor where RFA achieves sub-optimal temperatures [45] .…”
Section: Figure 2 Axial Computed Tomography Images Before and After Rmentioning
confidence: 99%